EPsmartcoat : Epoxy coating based green nanofillers - Siti Maznah, Kabeb; Azman, Hassan; Zurina, Mohamad; Zalilah, Shaher; Munirah, Mokhtar; Faiz, Ahmad (2021)
Bio-based epoxy coating which suitable for wide ranges applications. Affordable and excellent aesthetic value of green coating materials. Benefits of EPsmartcoat : flame retardancy and corrosion-free life (virtual freedom from maintenance and repair).